Physico-Morphological Characteristics and Oxidative Markers of Fresh Semen of Gir Bulls - Prajapati, Sunnykumar G.; Vala, Karsan B.; Singh, Vivek Kumar; Solanki, Gajendra B.; Chavda, Bhakti P. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present investigation was undertaken on four mature Gir bulls (4-6 years) maintained at University farm,  Junagadh for 4 months during hot summer season. Semen (n=6 ejaculate/bull) was collected using artificial  vagina once a week from each bull. The fresh ejaculates were evaluated for physical attributes and oxidative  stress markers in the seminal plasma. The overall mean values recorded based on 24 ejaculates for ejaculate  volume, sperm concentration, mass motility (0-5 scale), individual motility, sperm viability, sperm abnormality,  plasma membrane integrity (HOST reactive sperm), and acrosome integrity were 6.20 ± 1.27 mL, 1316.83 ±  155.07 million/ mL, 3.75 ± 0.20, 84.83 ± 0.94 %, 87.58 ± 1.07 %, 9.63 ± 0.83 %, 79.58 ± 1.01 % and 91.21 ± 0.52  %, respectively. There was a significant P
Keywords: Correlations; Gir bull semen; Oxidative biomarkers; Physico-morphological attributes